The Diocese of Narona (Ecclesia Naronitana) - Škegro, Ante (Arheološki vestnik, 2010)
The Christian community of the Diocese of Narona (Ecclesia Naronitana) deserves the most credit for the Christianization of the population living in the central part of the eastern Adriatic. From very early times, heralds of the faith brought Christianity to this region primarily along the transportation routes that connected Narona with Salona, and the valleys of the Neretva, Trebižat, and Bregava rivers in Hercegovina. St. Venantius, who died a martyr between 257 and 260 A.D. somewhere amongst the Delmatae population (inter Dalmatas), departed on his missions from the Narona region. The Diocese of Narona was founded before the appearance of the name of its only known bishop, Marcellus (Marcellus episcopus Ecclesiae Naronitanae). The early Christian basilicas in the inner hinterland of Narona were built and decorated according to the same architectural style. Accordingly, it can be reasonably presumed that the territories gravitating towards Narona and its basin were under the jurisdiction of the bishop of Narona. The islands of Mljet, korčula and Lastovo, the Pelješac peninsula and the coast around Makarska were all part of the Diocese of epidaurus (Ecclesia Epitauritana) and the Diocese of Salona (Ecclesia Salonitana), and after 533 A.D., of the Diocese of Muccurum (Ecclesia Muccuritana) as well. From at least the 6th century onwards, the (arch)bishop of Salona had supreme ecclesiastical authority in Dalmatia. Sacred buildings, primarily churches located in the inner hinterland, which managed to maintain their original function throughout the Middle Ages, indicate that some segments of Christianity that spread from Narona did not cease after the disappearance of Narona.